Logic Programming and Nonmonotonic Reasoning 13th International Conference, LPNMR 2015, Lexington, KY, USA, September 27-30, 2015. Proceedings - Calimeri, Francesco; Ianni, Giovambattista; Truszczynski, Miroslaw (Lecture Notes in Artificial Intelligence, 2015)
This volume contains the refereed proceedings of the 13th International Conference on Logic Programming and Nonmonotonic Reasoning, LPNMR 2015, held in September 2015 in Lexington, KY, USA. The 29 long and 11 short papers presented together with 3 invited talks, the paper reporting on the Answer Set Programming competition, and four papers presented by LPNMR student attendees at the doctoral consortium were carefully reviewed and selected from 60 submissions. LPNMR is a forum for exchanging ideas on declarative logic programming, nonmonotonic reasoning, and knowledge representation. The aim of the LPNMR conferences is to facilitate interactions between researchers interested in the design and implementation of logic-based programming languages and database systems, and researchers who work in the areas of knowledge representation and nonmonotonic reasoning.